Is recruitment more difficult with a placebo arm in randomised controlled trials? A quasirandomised, interview based study. Issue 7191 (24th April 1999) - Welton, A J; Vickers, M R; Cooper, J A; Meade, T W; Marteau, T M
Abstract: Objective : To investigate whether including a placebo arm in a clinical trial of hormone replacement therapy influenced women's stated willingness to participate. Design : Quasirandomised, interview based study. Setting : 10 group practices in the Medical Research Council's General Practice Research Framework. Participants : 436 postmenopausal women aged 45-64 who had not had a hysterectomy. Main outcome measures : Stated willingness to enter a trial and reasons for the decisions made. Results : Of 218 women told about the trial without a placebo arm, 85 (39%) indicated their willingness to enter compared with 65 (30%) of the 218 women told about the trial with the placebo arm (P=0.06). Part of this difference was due to explicit reluctance to take a placebo. Altruism and personal benefit were the reasons most frequently given for wanting to take part in a trial. The reasons most frequently cited for not wanting to take part were reluctance to restart periods, not wanting to take unknown or unnecessary tablets, or not wanting to interfere with present good health. Conclusion : For preventive trials the inclusion of a placebo arm may reduce patients' willingness to participate.